EDUKASI SIAGA BENCANA UNTUK MENINGKATKAN PERSEPSI LANSIA DI KELURAHAN PASIA NAN TIGO KECAMATAN KOTO TANGAH, PADANG - Hema Malini; Yuna Fitri; Boby Febri Krisdianto (BULETIN ILMIAH NAGARI MEMBANGUN, 2023)
Earthquake is a natural disaster that can occur suddenly and cause damage and loss of life. Therefore, it is important to have disaster preparedness to reduce the impact, especially on vulnerable groups such as the elderly. Therefore, a disaster education program is directed at increasing the elderly's perception of earthquake preparedness. This activity involved providing educational materials and simulations to 15 elderly people for one day. After the training, interviews were conducted to evaluate their perceptions regarding knowledge and attitudes towards disaster preparedness. Data were obtained through semi-structured interviews with 5 elderly people involved in the program. The results of the interviews revealed that the knowledge of the elderly about earthquakes still needs to be improved. Even so, most of them were able to demonstrate their ability to prepare disaster preparedness bags. However, there is potential to further enhance their knowledge and skills. This includes an understanding of the contents of a disaster preparedness bag, the actions to be taken during an earthquake, and their role in educating the community about disaster mitigation. It is hoped that this kind of program will have a long-term impact by increasing the understanding and awareness of the elderly on earthquake preparedness. Through an educational approach and their active involvement in simulation exercises, the elderly can become agents of change in improving disaster preparedness in the community.